Agronomic Characteristics of Three Varieties of Bell Pepper as Affected by the Same Level of Different Organic Fertilizers - Foja, Alice; Gervacio, Rebecca; Largueza, Efren (Romblon State University Research Journal, 2011)
The study was conducted to determine the effects of different organic fertilizers on the growth and yield of three varieties of bell pepper: majesty, trinity and kalahari. These three varieties of bell pepper were grown and fertilized with guano, chicken and carabao manure at the same level following the complete randomized block design with three treatments and three replications. The agronomic characteristics like height, number of fruits, and weight of fruits were gathered and analyzed using analysis of variance and Duncan Multiple range test at 5% level of significance. The findings show that there are no significant differences in height between varieties of bell pepper. There are significant differences on the mean number of fruits of bell pepper as affected by the same level of organic fertilizers. The number of fruits produced by plants fertilized with organic fertilizers are significantly higher compared to control. Plants fertilized with bat and chicken manure produced more fruits compared to those fertilized with carabao manure. The mean number of fruits of majesty and trinity variety is significantly higher compared to Kalahari. The effects of the organic fertilizers on the mean weight of fruits of three varieties are not significant; however, the mean weight of fruits of Majesty variety is significantly higher compared to Trinity and Kalahari varieties.